الصمود الجامعي لدى طلبة كلية التربية بجامعة القادسية - ميسر, نهلة عبدالهادي (lark, 2019)
The objective of the current research was to identify the level of university resilience and to detect the differences according to the variables (specialization, gender and grade). The research sample consisted of (250) male and female students who were selected in a random stratified manner. The results of the research showed that the students of the Faculty of Education at Qadisiya University have university resilience, as well as the existence of statistically significant differences according to the gender variable and the benefit of males, and the existence of statistically significant differences for the specialization variable and for the scientific specialization. In addition to the research results, the researcher presented a number of recommendations and suggestions for research